2021
DOI: 10.1108/jkm-09-2020-0730
|View full text |Cite
|
Sign up to set email alerts
|

A structured literature review of scientometric research of the knowledge management discipline: a 2021 update

Abstract: Purpose The purpose of this study is to conduct a structured literature review of scientometric research of the knowledge management (KM) discipline for the 2012–2019 time period. Design/methodology/approach A total of 175 scientometric studies of the KM discipline were identified and analyzed. Findings Scientometric KM research has entered the maturity stage: its volume has been growing, reaching six publications per month in 2019. Scientometric KM research has become highly specialized, which explains ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 163 publications
(149 reference statements)
0
23
1
Order By: Relevance
“…The case study shows a healthy interest in the KM discipline, as is indicated by the growing IAKM membership and the number of scientific outcomes that this CoP has apparently made it possible to produce. This statement contrasts earlier reports noting a decline in the volume of yearly studies on KM topics since 2015 (Serenko, 2021). Therefore, it is confirmed that participating in a scientific CoP like IAKM can really be beneficial for members, because it can boost collective knowledge building and, by this way, scientific production even higher www.ejkm.com 102 ©ACPIL than the average of scholars in the same field.…”
Section: Discussioncontrasting
confidence: 52%
“…The case study shows a healthy interest in the KM discipline, as is indicated by the growing IAKM membership and the number of scientific outcomes that this CoP has apparently made it possible to produce. This statement contrasts earlier reports noting a decline in the volume of yearly studies on KM topics since 2015 (Serenko, 2021). Therefore, it is confirmed that participating in a scientific CoP like IAKM can really be beneficial for members, because it can boost collective knowledge building and, by this way, scientific production even higher www.ejkm.com 102 ©ACPIL than the average of scholars in the same field.…”
Section: Discussioncontrasting
confidence: 52%
“…The increase in the scope of research works symbolizes the growing interest in the KM discipline and further confirms its status as a recognized management discipline. Moreover, as a discipline, KM is also recognized within the broader scientific community (Serenko, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…KM is considered a relatively young field (Serenko & Bontis, 2013). The deep historical roots of the discipline and the emergence of the first KM principles are described extensively in previous works (see, e.g., Serenko, 2021), and are not the focus of this article. It is a matter of historical record that KM has developed significantly since its establishment as a discipline in the late 1980s (Dalkir, 2005), and the literature records the evolution of KM over time (Handzic, 2017; Heisig, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another reason for the development of a dedicated ranking list of KM/IC journals pertains to the interdisciplinary nature of this domain (Serenko, 2013;Zavaraqi, 2016;Serenko, 2021). Interdisciplinary research refers to a "group of studies undertaken by scholars from two or more distinct scientific disciplines," which is "based upon a conceptual model that links or integrates theoretical frameworks from those disciplines, uses study design and methodology that is not limited to any one field, and requires the use of perspectives and skills of the involved disciplines throughout multiple phases of the research process" (Aboelela et al, 2007, p. 341).…”
Section: Introduction and Purpose Of The Studymentioning
confidence: 99%